(untitled) (Iraqi Journal of Science, 2024)
Cell-mediated immunity was estimated in diabetic patients by evaluation a levelof CD4 and CD8 in type 1 and 2 diabetic patients. Of the 33 patients with type 1diabetes mellitus 17 were males and 16 were females, as well as the type 2 diabetesmellitus patients were made up of 17 males and 16 females. Both groups attend theoutpatient Clinic in the National Diabetes Center, Al-Mustansiriya University.Besides that, the results of this study recorded that the mean of age among patientswith type 1 diabetes mellitus was 23.42 ± 4.25 y whereas mean of age amongsecond group was 51.27± 7.83 y with highly significant difference was noticedbetween them. In addition, the result of this study indicated that duration of diseaseamong type1diabetic patients was 7.15± 2.55 y while 11.45± 6.49 y among secondgroup with highly significant difference was noticed between them. For CD4lymphocytes, there was a highly significant decrease (P<0.001) in the percentagemeans of the CD4 cells in type2 diabetic patients, as compared with type 1 diabeticpatients. For CD8 lymphocytes, there was a decrease in the percentage of theselymphocyte in the peripheral blood of the type 2 diabetic patients, as compared withtype 1 diabetic patients with highly significant importance was recorded betweenthem. In conclusion, this study proved that impaired cell mediated immunity isprevalent in type 2diabetic patients, thus the change level of cytotoxic Tlymphocytes(CD8) and helper T- lymphocytes (CD4) might be responsible fordepressed immune response in patients with type 2 diabetes.